Nilai-Nilai Perjuangan dalam Cerpen “Hujan Pertama dari Kampung Kafir” Karya Silvester Petara Hurit (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the values ​​of struggle in the short story Hujan Pertama Dari Kampung Kafir by Silvester Petara Hurit. This study uses a descriptive qualitative method with data analysis techniques using a sociological approach. The results of the study indicate the values ​​of struggle in the short story Hujan Pertama Dari Kampung Kafir by Silvester Petara Hurit concluded as follows, 1) the struggle of indigenous people to maintain ancestral traditions, 2) the struggle to preserve local wisdom, 3) the struggle to maintain identity, 4) the struggle to find the meaning of faith, and 5) the struggle to maintain cultural symbols.